Mono‐ and Di‐Mesoionic Carbene‐Boranes: Synthesis, Structures and Utility as Reducing Agents - Stein, Felix; Kirsch, Marius; Beerhues, Julia; Albold, Uta; Sarkar, Biprajit (European journal of inorganic chemistry, 2021)
Mesoionic carbenes (MIC) of the 1,2,3‐triazol‐5‐ylidene type are currently popular ligands in organometallic chemistry. Their use in main group chemistry has been rather limited. In this contribution we present mono‐ and di‐MIC‐boranes with MICs based on triazolylidenes. The synthesis involves in‐situ deprotonation of the corresponding triazolium salts and their reaction with boranes to form the desired compounds. Whereas this reaction route worked well for all triazolium salts derived from the 1,4‐regioisomer of the triazoles, for the methlyene‐bridged bi‐triazolium salt derived from a 1,5‐substiuted triazole, we observed the unexpected decomposition of the bi‐triazolium and the formation of a triazole‐borane with a new N−B bond. All compounds were characterized via multinuclear NMR spectroscopy, mass spectrometry, and single crystal X‐ray diffraction. Furthermore, the MIC‐boranes were used as reducing agents for the reduction of the C=O of aldehydes to the corresponding alcohols. A series of MIC‐borane adducts are presented. In one case the unexpected formation of a triazole‐borane adduct through the decomposition of a bitriazolium salt was observed. The compounds were used for the reduction of aldehydes to alcohols in the presence of Lewis acids.